Modal characterization of a helicopter stabilizer from flight test campaign with externally mounted accessory - Ambrosio, D. Ricardo; Camargo, E. Alexandre; Candido de Sousa, V. [UNESP]; Castillo Zúñiga, D. Fernando [UNESP]; Sartorato, M. [UNESP]; Costa, N.; Luiz Oliveira, [UNESP] (My University, 2024)
This study presents the modal characterization of the horizontal stabilizer and lateral fin of an AS365 helicopter with an externally mounted accessory flown at several different flight conditions. To investigate empennage vibrations, acceleration flight data were acquired for the helicopter with and without the accessory for a number of different flight conditions. Operational Modal Analysis with both the Subspace Stochastic Identification and Curve Frequency Domain Decomposition techniques was considered for the acceleration data analysis. Modal Assurance Criterion was also applied. The modal parameters (natural frequencies, mode shapes and damping ratios) were identified from the singular value amplitude peaks and the corresponding response autocorrelation functions for frequencies up to 250 Hz. The first ten modes were successfully identified, what includes pure bending and torsion modes in the isolated horizontal stabilizer and lateral fin, and coupled modes involving both horizontal stabilizer and lateral fin.